2018
DOI: 10.1136/jmedgenet-2018-105315
|View full text |Cite
|
Sign up to set email alerts
|

Genetic obesity: next-generation sequencing results of 1230 patients with obesity

Abstract: NGS-based gene panel analysis in patients with obesity led to a definitive diagnosis of a genetic obesity disorder in 3.9% of obese probands, and a possible diagnosis in an additional 5.4% of obese probands. The highest yield was achieved in a selected paediatric subgroup, establishing a definitive diagnosis in 12 out of 164 children with severe early onset obesity (7.3%). These findings give a realistic insight in the diagnostic yield of genetic testing for patients with obesity and could help these patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 28 publications
(12 reference statements)
6
45
0
2
Order By: Relevance
“…The prevalence of pathogenic variants in MC4R in our cohort was 2% (2/92), which is comparable to previous reports (7,(10)(11)(12)(13)(14). The patients in our study with the novel MC4R frameshift deletion had severe childhood obesity and hyperphagia.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The prevalence of pathogenic variants in MC4R in our cohort was 2% (2/92), which is comparable to previous reports (7,(10)(11)(12)(13)(14). The patients in our study with the novel MC4R frameshift deletion had severe childhood obesity and hyperphagia.…”
Section: Discussionsupporting
confidence: 87%
“…We performed a literature search to identify genes related to the melanocortin pathway and the development of the hypothalamus (1,5,12,18,19,21,(26)(27)(28)(29)(30)(31)(32)(33). The 24 genes included in the panel were: (1) genes in which variants have previously been reported to cause or associate with obesity (ADCY3, BDNF, CPE, GRPR, LEP, LEPR, LRP2, MC3R, MC4R, MRAP2, MYT1L, NPY, NTRK2, PCSK1, POMC, SH2B1, SIM1, TUB) and (2) genes previously reported in animal models/linkage analysis/CNV studies to be involved in the melanocortin pathway or development of hypothalamus (ARNT2, ISL1, NEUROG3, OTP, OXT, POU3F2).…”
Section: Genes In the Panelmentioning
confidence: 99%
See 1 more Smart Citation
“…Although obesity is suggested to be a multifactorial condition, mostly caused by our changing obesogenic environment, an underlying genetic defect has been reported in approximately 2%-15% of morbidly obese patients (Foucan et al, 2017;Kleinendorst et al, 2018). Mutations in the melanocortine-4 receptor (MC4R) gene are the most common cause of monogenic obesity, with a prevalence of 0.5%-5.8%, with the highest values expected in cohorts with early onset obesity (Valette et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As new therapies are arising that target specific types of obesity, we here plead for screening for genetic obesity in a subgroup of patients who have a high clinical suspicion for these types of genetic obesity. A recent study found a confirmed diagnosis of genetic obesity in 3.9% of patients who were clinically suspected of genetic obesity . Indications for genetic screening include an early age of onset, below 5 years of age, (or in adult populations a prepubertal onset), a family history with striking weight differences between family members (which may indicate monogenic obesity), and severe hyperphagia (which can be seen in monogenetic obesity‐with and without intellectual deficit).…”
Section: Assessment Of Obesity—clinical Historymentioning
confidence: 99%